Efficacy of Fungicides on Seed Mycoflora of Groundnut at Different Storage Periods - Srinivas, A.; Pushpavathi, B.; Lakshmi, B. K. M.; Shashibushan, V. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Seed Research & Technology Centre, Professor Jayashankar Telangana State Agricultural University, Hyderabad, Telangana, India during January-June, 2016.The efficacy of 7 fungicides viz., captan (0.25%), mancozeb (0.25%), carboxin+thiram (0.3%), carbendazim (0.2%), benomyl (0.2%), tebuconazole (0.1%) and carbendazim+iprodione (0.2%) against seed mycoflora of groundnut at recommended dosages and at different storage periods (immediately after treatment, 1 day after treatment, 1 week after treatment, 2 weeks after treatment, 3 weeks after treatment, 1 month after treatment, 2 months after treatment and 3 months after treatment) were studied using standard blotter method. Treated seeds (of different storage periods) were incubated for 7 days and data on percent seed infection and frequency were recorded. Among the fungicides tested, seed treatment with carboxin+thiram (21.19%) was found significantly superior in reducing the percent seed infection followed by captan (24.00%) and the least effective was carbendazim (71.91%). A total of 13 seedborne fungi belonging to 10 genera viz., Macrophomina phaseolina, Rhizoctonia spp., Rhizopus spp., Aspergillus flavus, Aspergillus niger, Aspergillus ochraceus, Aspergillus ustus, Alternaria spp., Fusarium spp., Penicillium spp., Trichoderma spp., Chaetomium spp. and Cladosporium spp. were recovered from untreated and treated seeds at different storage periods. The percent seed infection by different seed mycoflora increased with the increase in storage period. However, there was a gradual decline in field mycoflora viz., Macrophomina phaseolina and Rhizoctonia spp. and gradual increase in storage mycoflora viz., Aspergillus spp., Cladosporium spp., Rhizopus spp., Penicillium spp. etc. found with the increase in storage period.